Oxidative damage to nucleic acids and benzo(a)pyrene-7,8-diol-9,10-epoxide-DNA adducts and chromosomal aberration in children with psoriasis repeatedly exposed to crude coal tar ointment and UV radiation - Borska, Lenka; Andrýs, Ctirad; Krejsek, Jan; Palicka, Vladimir; Chmelarova, Marcela; Hamakova, Kvetoslava; Kremlacek, Jan; Fiala, Zdenek (Oxidative medicine and cellular longevity, 2014)
The paper presents a prospective cohort study. Observed group was formed of children with plaque psoriasis (n=19) treated by Goeckerman therapy (GT). The study describes adverse (side) effects associated with application of GT (combined exposure of 3% crude coal tar ointment and UV radiation). After GT we found significantly increased markers of oxidative stress (8-hydroxy-2'-deoxyguanosine, 8-hydroxyguanosine, and 8-hydroxyguanine), significantly increased levels of benzo[a]pyrene-7,8-diol-9,10-epoxide (BPDE) DNA adducts (BPDE-DNA), and significantly increased levels of total number of chromosomal aberrations in peripheral lymphocytes. We found significant relationship between (1) time of UV exposure and total number of aberrated cells and (2) daily topical application of 3% crude coal tar ointment (% of body surface) and level of BPDE-DNA adducts. The findings indicated increased hazard of oxidative stress and genotoxic effects related to the treatment. However, it must be noted that the oxidized guanine species and BPDE-DNA adducts also reflect individual variations in metabolic enzyme activity (different extent of bioactivation of benzo[a]pyrene to BPDE) and overall efficiency of DNA/RNA repair system. The study confirmed good effectiveness of the GT (significantly decreased PASI score).
Keywords: keratolytika; Benzo(a)pyrene; psoriáza; ultrafialové záření; Child; Adolescent; Child, Preschool; Humans; Ultraviolet Rays; lidé; Oxidative Stress; masti; prospektivní studie; Lymphocytes; dítě; 7,8-Dihydro-7,8-dihydroxybenzo(a)pyrene 9,10-oxide; DNA Adducts; Prospective Studies; Female; Psoriasis; lymfocyty; Cohort Studies; Ointments; DNA Damage; Male; mladiství; benzopyren; Keratolytic Agents; adukty DNA; předškolní dítě; Coal Tar; Chromosome Aberrations; poškození DNA; 7,8-dihydro-7,8-dihydroxybenzo(a)pyren 9,10-oxid; DNA; oxidační stres; ženské pohlaví; mužské pohlaví; kohortové studie; dehet uhelný; chromozomální aberace